2011
DOI: 10.1016/j.yexmp.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of a specific receptor for lipocalin2 (solute carrier family 22 member 17, SLC22A17) and its prognostic significance in endometrial carcinoma

Abstract: Background: We previously reported the overexpression of lipocalin2 (LCN2), a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
4
27
0
Order By: Relevance
“…While there is a limited amount of research published for SLC22A17, recent reports have indicated that its expression is correlated with malignancy. For instance, overexpression of both LCN2 and SLC22A17 has been associated with a worse prognosis in gliomas, hepatocellular and endometrial cancer [4749]. Moreover, we observed that Lcn2 is also upregulated in the serum after HFD consumption in animals that express pancreas-specific mutant KRas .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…While there is a limited amount of research published for SLC22A17, recent reports have indicated that its expression is correlated with malignancy. For instance, overexpression of both LCN2 and SLC22A17 has been associated with a worse prognosis in gliomas, hepatocellular and endometrial cancer [4749]. Moreover, we observed that Lcn2 is also upregulated in the serum after HFD consumption in animals that express pancreas-specific mutant KRas .…”
Section: Discussionmentioning
confidence: 71%
“…Both SLC22A17 and LRP2 have been reported to bind and mediate the cellular uptake of LCN2 [4345]. While SLC22A17 has been shown to bind specifically to LCN2, LRP2 also binds numerous structurally unrelated molecules including aprotinin, vitamin D3, transferrin and lactoferrin [46, 47]. While there is a limited amount of research published for SLC22A17, recent reports have indicated that its expression is correlated with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased expression of CLU thus promotes the cancerous disease condition. LCN2 encodes a 25 kDa secretory protein involved with iron-transportation and contributes to endometrial carcinoma [66]. Moreover, it is a key molecule in various signalling pathways (Additional file 4).…”
Section: Resultsmentioning
confidence: 99%
“…Validation by immunohistochemistry confirmed the increase of LCN2 expression from atypical endometrial hyperplasia to carcinomas [22]. High expression of LCN2 protein together with its receptor SLC22A17 has been related to poorer prognosis among endometrial cancer patients [23]. LCN2 mRNA levels have been associated with different EMT-related genes in a study of endometrial hyperplasia [24].…”
Section: Introductionmentioning
confidence: 98%